2012
DOI: 10.1007/s00572-012-0465-8
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi reduce the differences in competitiveness between dominant and subordinate plant species

Abstract: In grassland communities, plants can be classified as dominants or subordinates according to their relative abundances, but the factors controlling such distributions remain unclear. Here, we test whether the presence of the arbuscular mycorrhizal (AM) fungus Glomus intraradices affects the competitiveness of two dominant (Taraxacum officinale and Agrostis capillaris) and two subordinate species (Prunella vulgaris and Achillea millefolium). Plants were grown in pots in the presence or absence of the fungus, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 55 publications
2
36
1
1
Order By: Relevance
“…Thirdly, greater abundance of AMF in microbial communities from extensively managed grassland might have reduced the competitive ability of dominant species (Mariotte et al . ), thus increasing plant community diversity (Van der Heijden et al . ), while increasing the competitive ability of legumes (Scheublin, Van Logtestijn & Van der Heijden ; Sabais et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, greater abundance of AMF in microbial communities from extensively managed grassland might have reduced the competitive ability of dominant species (Mariotte et al . ), thus increasing plant community diversity (Van der Heijden et al . ), while increasing the competitive ability of legumes (Scheublin, Van Logtestijn & Van der Heijden ; Sabais et al .…”
Section: Discussionmentioning
confidence: 99%
“…They are very important determinants on the earlier successional phase by stabilizing perennial forb seedlings (Gange et al, 1993). It triggers this effect by reducing competition among species that facilitate coexistence in the critical phase of community development (Mariotte et al, 2013). Furthermore there are evidences showing that, not only the vegetation can change during succession, but simultaneously soil fungal community, suggesting a sensitive feed-back between plants and soil fungi ( Sikes et al, 2012, Cutler et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…subsecundus was reduced in the presence of Glomus cubense. These effects have been demonstrated in pot experiments where it has been suggested that less favourable AM fungi could reduce the dominance of some plant species in grassland (Mariotte et al 2013). In addition, seasonal changes in the composition of AM fungi in roots can occur (Santos et al 2006), and AM fungal diversity can be affected by plant species composition (Johnson et al 2004).…”
Section: Host Plant Preferencesmentioning
confidence: 91%